PENGEMBANGAN PRODUK UMKM OLAHAN IKAN ASIN MELALUI PELATIHAN PACKAGING DAN PEMASARAN ONLINE - Aan Widiyono; Nur Khomsanah; Muhammad Idrus Sholahuddin; Muhammad Ridwan; Adrian Malta (Universitas PGRI Yogyakarta, 2022)
This service aims to develop MSME products for processing boiled salty through packaging training and online marketing during the pandemic with various problems including decreased sales results, uncertain weather, and fish supply. Based on this problem, the KKN and DPL groups formulated to conduct product packaging training, and promotional activities and expand product marketing offline and online. This service was carried out from February to March 2021 at the UMKM salted fish processing business, UD. Jarot Mandiri. The results obtained are improving the results of packaging for MSMEs that are up to date and adjusted to market demand, the results of packaging training such as in processed packaging techniques for crackers and salted fish. Another result that has been done is facilitating marketing in the marketplace via Instagram, Facebook, Tokopedia, Shopee, etc. In addition, high enthusiasm is seen in MSME entrepreneurs who are increasingly motivated and dare to compete with processed fish products from outside the Jepara area. Keywords: UMKM Products, Packaging Training, Online Marketing